Molecular and subcellular mechanisms of vital macrophage extracellular trap formation - Lee, Yongchan; Brenner, Max; Aziz, Monowar; Wang, Ping (Frontiers in Immunology, 2025)
Macrophage extracellular traps (METs) are a poorly understood process beneficial for infection control but detrimental in inflammation, autoimmunity and cancer. Our research shows that viable macrophages release METs even when plasma membrane lysis is blocked. We demonstrate, for the first time, that nuclear DNA is extruded directly into the cytoplasm through Gasdermin D pores on the nuclear envelope. Gasdermin D pore formation was triggered by extracellular cold-inducible RNA-binding protein, which activates the TLR4 signal transduction pathway. This DNA is processed in the cytoplasm, enters the vesicular transport system aided by autophagic flux and the Endosomal Sorting Complex. The DNA then enters the lysosomal compartment, where it undergoes histone 3 citrullination, forms nascent traps containing myeloperoxidase, and is released to the extracellular space. Our study provides valuable insights into vital MET formation and its mechanism that will enable future studies on the role of METs in health and disease.